Peran Guru dalam Penerapan Pembelajaran Mendalam (Deep Learning) di Kelas Reguler dan Kelas Inklusi - Trisanani, Novy; Sugiyanta, Geyol; Utami, Asih; Utami, Wulan Tri Puji (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
Deep learning emphasizes conceptual understanding, critical thinking, and the interconnection between topics to create meaningful learning experiences. The aim of this study is to identify the role of teachers in implementing deep learning in both regular and inclusive classrooms. This study employs a literature review method by analyzing 32 sources, consisting of relevant journal articles and academic books. The data were analyzed descriptively and qualitatively using a thematic approach based on the main themes: teacher roles and instructional strategies. The findings indicate that teachers play a central role in applying deep learning. In regular classrooms, teachers act as designers of differentiated instruction and facilitators of dialogue that support individual student needs. Meanwhile, in inclusive classrooms, teachers are also required to implement Universal Design for Learning (UDL), collaborate with teaching assistants, and create an inclusive learning environment. Pedagogical competence, empathy, and the ability to collaborate are key factors in the successful implementation of deep learning.Pembelajaran mendalam (deep learning) menekankan pemahaman konsep, berpikir kritis, dan keterkaitan antarmateri untuk menciptakan pembelajaran yang bermakna. Pembelajaran mendalam (deep learning) menekankan pemahaman konsep, berpikir kritis, dan keterkaitan antarmateri untuk menciptakan pembelajaran yang bermakna. Tujuan kajian ini adalah untuk mengidentifikasi peran guru dalam menerapkan pembelajaran mendalam di kelas reguler dan inklusi. Metode yang digunakan adalah studi literatur dengan menganalisis 32 sumber, terdiri dari artikel jurnal dan buku relevan. Data dianalisis secara deskriptif-kualitatif melalui pendekatan tematik berdasarkan tema utama, yaitu peran guru dan strategi pembelajaran. Hasil kajian menunjukkan bahwa guru memiliki peran sentral dalam menerapkan pembelajaran mendalam. Di kelas reguler, guru bertindak sebagai perancang pembelajaran diferensiatif dan fasilitator dialog yang mendukung kebutuhan individu. Sementara itu, di kelas inklusi, guru juga perlu menerapkan Universal Design for Learning (UDL), berkolaborasi dengan pendamping, dan menciptakan lingkungan belajar yang inklusif. Kompetensi pedagogis, empati, dan kemampuan berkolaborasi menjadi kunci utama.